(untitled) (Chest & Heart Journal, 2021)
Dieulafoy’s lesions are a rare but challenging cause of upper GI bleeding due to their intermittent nature. This lesions contribute approximately 6% of non-variceal upper GI bleeds and 1-2% of all GI bleeding. This quiescent lesions are easily overlooked on endoscopy and the bleeding lesions are occationally misidentified. Increased awareness and advances in the endoscopic techniques are important for accurate diagnosis. A case of 32 years young man present with Dieulafoy,s lesion in proximal stomach has been described here. Chest Heart J. 2020; 44(2) : 106-111